THE INFLUENCE QUALITY OF FINANCIAL REPORTS FOR LENDING AND PROSPECTS OF IMPLEMENTATION SAK ETAP IN THE SMALL AND MEDIUM ENTERPRISES (SMES) IN PEKANBARU CITY - Gusnardi '; Jawanri Citra PS; Fenny Trisnawati (Program Studi Pendidikan Ekonomi Universitas Riau, 2015)
This study aims to determine the influence of the quality of the financial reports of the credit giving and the prospect of the implementation of financial accounting standards entities without public accountability (SAK ETAP) on SMEs in the Pekanbaru City. The research data obtained from questionnaires were returned and interviews to 100 100 SMEs in the Pekanbaru City. These results indicate that the quality of financial reports SMEs do not influence the amount of credit received by SMEs .This is caused by the low quality of financial reports of SMEs so that banks are still doubt of the relevance and reliability of financial reporting SMEs. The prospect implementation for SMEs in improving the quality of financial reports is limited because of the lack of understanding SMEs on SAK ETAP.Keywords: Quality of Financial Reports, SMEs, SAK- ETAP